Emanuel Zitta. About the Career and the Work of an Officer of the Corps of Engineer in the Half of the 19th Century (Theatrum historiae, 2016)
The presented study wants to enrich number of works that focus on “common” officers of the Austrian army that came from burgher classes. The aim of the study is neither to compare fates of other soldiers nor to analyse sociological or national setup of the corps of officers. It will rather simply offer a view on the career of one of officers of an engineer brigade. This career will be followed in a context of a development of the corps of engineer in the first half of the 19th century.
Keywords: Austrian army; daily life; engineer corps